Nothing Alike - Moor, Zewlan; Cheong, Peter (Richmond, Victoria : Bright Light/Hardie Grant Children's Publishing, 2023)
"Reuben thinks it's impossible to tell Esme and Eunwoo apart! They both have the same dark hair, are both short, and they even wear the same school uniform. Except that once Reuben starts to think about it, of course he knows who is who. But just as he starts to learn who's who, the girls have a surprise in store for him..." -- publisher.
Keywords: Asians -- Juvenile fiction; Children's stories, Australian; Friendship -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Lookalikes -- Juvenile fiction; Perception -- Juvenile fiction; School children -- Juvenile fiction; Stereotypes (Social psychology) -- Juvenile fiction; Electronic books